2021
DOI: 10.18805/ijar.b-3841
|View full text |Cite
|
Sign up to set email alerts
|

Prospects and Application of Nanotechnology for Diagnosis of Tuberculosis in Livestock: A Review

Abstract: Tuberculosis (TB) is an infectious and contagious disease caused by various strains of Mycobacterium and the foremost leading cause of death of animal and human population worldwide. Currently available conventional and modern diagnostic techniques are useful but they are neither rapid nor cost effective for early and accurate diagnosis, represents a cornerstone to eradicate TB worldwide by 2030. To overcome this awful situation an innovative strategy i.e. nanotechnology is helpful for early diagnosis of tuber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Nowadays, ticks (parasitic insects) are the major problems that cause huge economic losses in the dairy and livestock production sector worldwide (Zaheer et al, 2022). In addition, researchers investigated the potential of nanotechnology in the eradication of tuberculosis worldwide in livestock (Bharti et al, 2022). Recently, Dhoolappa et al, (2022) reported that the novel nano-bioscaffolds have excellent wound-healing properties in animals.…”
Section: Detection and Removal Of Pathogensmentioning
confidence: 99%
“…Nowadays, ticks (parasitic insects) are the major problems that cause huge economic losses in the dairy and livestock production sector worldwide (Zaheer et al, 2022). In addition, researchers investigated the potential of nanotechnology in the eradication of tuberculosis worldwide in livestock (Bharti et al, 2022). Recently, Dhoolappa et al, (2022) reported that the novel nano-bioscaffolds have excellent wound-healing properties in animals.…”
Section: Detection and Removal Of Pathogensmentioning
confidence: 99%